1988
DOI: 10.1007/bf01268883
|View full text |Cite
|
Sign up to set email alerts
|

Changes induced by aging and drug treatment on cerebral enzymatic antioxidant system

Abstract: The age-related modifications of the participants to the cerebral enzymatic antioxidant system (superoxide dismutase, glutathione peroxidase, glutathione reductase, glucose-6-phosphate dehydrogenase, 6-phosphogluconate dehydrogenase) were evaluated in four brain regions from male Wistar rats aged 5, 10, 15, 20, 25, 30, and 35 months. Both the specific enzyme activity and the profile of any enzyme tested markedly differ with age according to the region examined: parieto-temporal cortex, caudate-putamen, substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…In the majority of studies, a comprehensive approach was not selected, and many contradictory results have been reported. Thus, total SOD, Se-GPx, or GR, decreased (Hothersall et al, 1981;Benzi et al, 1988a;Vanella et al, 1989), did not change (Keilogg and Fridovich, 1976;Mizuno and Ohta 1986;Cand and Verdetti, 1989), or even increased (Hothersall et al, 1981;Danh et al, 1983;Victorica, 1984;Tayarami et al, 1989) in the brains of aged rats. Brain cumene-OOH GPx and CAT were smaller in the brain of old compared with young rats (Cand and Verdetti, 1989).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In the majority of studies, a comprehensive approach was not selected, and many contradictory results have been reported. Thus, total SOD, Se-GPx, or GR, decreased (Hothersall et al, 1981;Benzi et al, 1988a;Vanella et al, 1989), did not change (Keilogg and Fridovich, 1976;Mizuno and Ohta 1986;Cand and Verdetti, 1989), or even increased (Hothersall et al, 1981;Danh et al, 1983;Victorica, 1984;Tayarami et al, 1989) in the brains of aged rats. Brain cumene-OOH GPx and CAT were smaller in the brain of old compared with young rats (Cand and Verdetti, 1989).…”
Section: Discussionmentioning
confidence: 90%
“…Part of these discrepancies can be attributed to differences in the strain or age selected. Thus, in some studies, not fully mature animals (4 months) were selected as "young" (Cand and Verdetti, 1989), whereas in other works clear decreases were observed in very old rats (35 months), but not in senescent individuals (25 months) (Benzi et al, 1988a). Nevertheless, it seems from these data that aging in the rat is not accompanied by increases of oxidative stress and decreases in antioxidant defenses in a way so marked as in the housefly.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, it wasn't until the late 1980s that it was found to induce cerebral antioxidant enzyme activation (Benzi et al, 1988;Gorini et al, 1988), thereby making it a candidate neuroprotective drug. To this end, Favit et al (1993) evaluated whether DECP could prevent induced neurotoxicity via several experimental approaches, including aged-related neurodegeneration and glutamate-induced neurotoxicity.…”
Section: Dihydroergocryptine (Decp)mentioning
confidence: 97%
“…Benzi et al reported that activities of GSH-PX, glutathione reductase, and SOD decrease in the parieto-temporal cortex, striatum, substantia nigra, and thalamus in rats aged 15–30 months of age compared to younger rats (Benzi et al, 1988). …”
Section: 3 Factors Affecting Antioxidant Enzyme Expressionmentioning
confidence: 99%